Factorial Structure of Trunk Motor Qualities and Their Association with Explosive Movement Performance in Young Footballers - Jasminka Tomčić; Nejc Šarabon; Goran Marković (MDPI AG, 2021)
This study examined the factorial structure of trunk motor qualities and their associations with explosive muscular performance of football players. Ninety-one young male football players (age: 15-21 years; body height: 1.78 ± 0.07 m; body mass: 70.3 ± 7.5 kg) performed a series of tests: four standing and four seated isometric trunk strength tests, seven trunk power (medicine ball throwing) tests, four trunk endurance tests and four explosive movement performance tests. A principal component factor analysis (PCA) was used to determine the structure of trunk motor qualities, and correlational analyses were used to assess linear associations between trunk motor qualities and explosive performance. The PCA revealed four independent factors-trunk power, standing and seated isometric trunk strength, and trunk muscle endurance. Only trunk power had significant moderate, logically positive associations with sprint and vertical jump performance (common variance: 25-36%), while other associations between trunk motor factors and explosive movement performance were generally low to very low. These results indicate that trunk muscle functions of football players can be described with three independent motor qualities-trunk power, trunk strength and trunk muscle endurance, with only trunk power being moderately associated with players' sprinting and jumping performance.